THE INFLUENCE OF THE 4.0 INDUSTRIAL REVOLUTION ERA ON HUMAN RESOURCE COMPETENCE AND PERFORMANCE (CASE STUDY AT PT. SERMANI STEEL IN MAKASSAR) - Eben Haezer B. Patandean; Sumardi Lasise; Wardhani Hakim (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This research is a study that is in the direction of knowing the influence of the industrial revolution era 4.0 on human resources competence and performance. The sample in this study is all permanent employees of PT Sermani Steel company in Makassar City which numbered 95 employees, the size of the sample that can represent the population to be studied is as many as 83 respondents. The method of analysis used is simple regression analysis, with the t-test as a research hypothesis test. Based on the results of the research that has been done, it can be known partially the free variables that exist in the industrial revolution era 4.0 had a significant effect on competence and h e r performance, the industrial revolution era 4.0 had a significant effect on h e r performance and the results of the study also proved there was an influence of competence on hr performance in PT. Sermani Steel in Makassar City.